2014
DOI: 10.3390/f5040744
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Wave Velocity as a Selection Trait in Eucalyptus nitens

Abstract: Previous studies in Eucalyptus nitens have revealed favourable genetic correlations exist between acoustic wave velocity (AWV) in standing trees and modulus of elasticity (MOE), which can determine the suitability of trees for structural timber and/or engineered wood products. This study investigates the strength and stability of genetic variation in standing tree AWV across a range of environments in Tasmania, where there are a number of large plantation estates and breeding trials. Trees under study were fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
4
15
2
1
Order By: Relevance
“…The additive genetic correlation between AWV and diameter (0.58) was within the range of estimates for E. nitens reported by Blackburn et al (2014;0.18, 0.20, 0.51 and 0.71), Furthermore, the positive additive genetic correlations of diameter with cellulose content (0.48) and pulp yield (0.38) were favourable and in keeping with recent studies by Stackpole et al (2010;0.52 between diameter and pulp yield), Costa e Silva et al (2009); 0.12 between diameter and pulp yield across multiple trials) and Apiolaza et al (2005;0.61 between diameter and cellulose content). However, these positive correlations were not significantly different from zero, except in the case of diameter with cellulose content in the current study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The additive genetic correlation between AWV and diameter (0.58) was within the range of estimates for E. nitens reported by Blackburn et al (2014;0.18, 0.20, 0.51 and 0.71), Furthermore, the positive additive genetic correlations of diameter with cellulose content (0.48) and pulp yield (0.38) were favourable and in keeping with recent studies by Stackpole et al (2010;0.52 between diameter and pulp yield), Costa e Silva et al (2009); 0.12 between diameter and pulp yield across multiple trials) and Apiolaza et al (2005;0.61 between diameter and cellulose content). However, these positive correlations were not significantly different from zero, except in the case of diameter with cellulose content in the current study.…”
Section: Discussionsupporting
confidence: 85%
“…Selection based on AWV is likely to result in positive indirect responses in other wood properties, including MOE and basic density, as suggested by genetic correlation estimates from E. nitens (Blackburn et al 2012;Blackburn et al 2010;Blackburn et al 2014). Similarly, in addition to pulp yield, QTL for AWV were co-located with numerous growth and other wood property traits within and among families, consistent with strong correlations among chemical wood properties in E. globulus (e.g.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Density, diameter at age 2 (growth), volumetric shrinkage, acoustic velocity and stiffness all have significantly large heritability, suggesting that breeding for these traits is achievable. The heritabilities are similar to those reported for other eucalypt species (Hung et al 2014;Hein et al 2012;Blackburn et al 2010;Blackburn et al 2014;Hamilton et al 2008). Wood processors pay premiums for stable and stiff timber, while forest growers often prefer to have fastgrowing trees as to shorten rotation lengths increasing profitability.…”
Section: Resultssupporting
confidence: 75%
“…The two species examined in these studies have been previously shown to be genetically stable in different environments (Callister et al 2011;Blackburn et al 2014). Strong race stability and inter-site additive genetic correlations for additive effects in the traits examined were also high, indicating a lack of genotype x environmental interaction at the family level.…”
Section: Introductionmentioning
confidence: 85%